A Review of Free Cloud-Based Anti-Malware Apps for Android - Walls, Jason; Choo, Kim-Kwang Raymond (2015 IEEE Trustcom/BigDataSE/ISPA, 2015)
The traditional way of protecting a system against malicious threats and loss of personal data by using locally installed anti-malware software is unlikely to work on mobile devices due to the changing threat landscape and the mobile device resource limitations (e.g. storage and battery life). A number of anti-malware providers have migrated to the cloud where the computationally demanding tasks of analyzing malware is conducted by cloud-based server. However, the effectiveness of these anti-mobile apps has not been studied. Therefore, in this paper, we evaluate the effectiveness of ten popular free cloud-based anti-malware apps using a known Android malware dataset. We hope that this research will contribute towards a better understanding of the effectiveness of Android cloud-based anti-malware apps.